Drót 1. adás
1.Sarajevo: footage of bombing May 27, 1992, NATO campaign, bombing of a market place in Sarajevo, involving Russia in managing the conflict, Hungary’s foreign politics concerning Yugoslavia. 2. Sudan: civil war, interview with Gáspár Bíró, UN Special Rapporteur. 3. Gábor Kuncze evaluates the past four years. 4. The foundry at Diósgyőr: privatization, bankruptcy, lay-offs, trade union, works councils. 5. Consolidation of the bank system: interview with György Surányi. 6. Justice Law: firings in 1956, retaliation. 7. Preview of next Drót program.